Exiles in a land of liberty : Mormons in America, 1830-1846 - Winn, Kenneth H. (Studies in religion (Chapel Hill, N.C.), 1989)
Using the concept of ""classical republicanism"" in his analysis, Kenneth Winn argues against the common view that the Mormon religion was an exceptional phenomenon representing a countercultural ideology fundamentally subversive to American society. Rather, he maintains, both the Saints and their enemies affirmed republican principles, but in radically different ways. Winn identifies the 1830 founding of the Mormon church as a religious protest against the pervasive disorder plaguing antebellum America, attracting people who saw the libertarianism, religious pluralism, and market capi.